2017
DOI: 10.1093/eurpub/ckx113
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable hospitalization among migrants and ethnic minority groups: a systematic review

Abstract: AH has been used, mostly in the US, to compare different racial/ethnic groups, while it has never been used in Europe to assess migrants' access to PHC. Studies comparing AH rates between migrants and natives in European settings can be helpful in filling this lack of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 58 publications
4
24
1
Order By: Relevance
“… 26 Most such research has been in the USA and New Zealand. 27 In the USA, where ethnicity and race are more strongly related to socioeconomic circumstances than in the UK, studies have found higher amenable mortality among black than white populations. 28 , 29 Similarly, ethnic and racial minorities in the USA have been found to have an increased risk of ambulatory care-sensitive conditions 30 , 31 and lower levels of receipt of high-quality treatment white ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Most such research has been in the USA and New Zealand. 27 In the USA, where ethnicity and race are more strongly related to socioeconomic circumstances than in the UK, studies have found higher amenable mortality among black than white populations. 28 , 29 Similarly, ethnic and racial minorities in the USA have been found to have an increased risk of ambulatory care-sensitive conditions 30 , 31 and lower levels of receipt of high-quality treatment white ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“… 35 The evidence is especially scarce within Europe. A 2017 systematic review 27 found no studies of avoidable hospital admissions within Europe by ethnicity, race, or migration status, and only three longitudinal studies worldwide. A study by de Bruijne and colleagues, 11 which found ethnic variations in unplanned readmissions and excess length of stay in the Netherlands, seems to be the only study to investigate the quality of health-care delivery by ethnicity in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the consequences of cultural and linguistic diversity for the care offered by health services, such as cultural misunderstandings, increased stress and anxiety of professionals or language barrier [6][7][8][9]. The different characteristics of the migrant population can hinder patient access and/or decrease the quality of healthcare received [10], leading to considerations of the foreign patient as complicated [11] and problematic [12]. From the nursing perspective, theories and models have emerged that aim to improve health care for this diverse population [6,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in USA, New Zealand and Scotland have found higher risk of ACSC admission for many ethnic minorities compared with the white majority populations. [4][5][6] A recent Scottish study found that South Asian groups had higher risk of ACSC admission compared with the white majority group. 4 The primary objective of this study was to elucidate whether ethnicity plays an important role in ACSC among emergency admissions in England at a national and regional level.…”
Section: Introductionmentioning
confidence: 99%